2017
DOI: 10.1038/s41598-017-01851-9
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Efficacy of a Novel Sodium Channel Modulator in Dravet Syndrome

Abstract: Dravet syndrome, an epileptic encephalopathy affecting children, largely results from heterozygous loss-of-function mutations in the brain voltage-gated sodium channel gene SCN1A. Heterozygous Scn1a knockout (Scn1a +/−) mice recapitulate the severe epilepsy phenotype of Dravet syndrome and are an accepted animal model. Because clinical observations suggest conventional sodium channel blocking antiepileptic drugs may worsen the disease, we predicted the phenotype of Scn1a +/− mice would be exacerbated by GS967,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 41 publications
1
65
0
Order By: Relevance
“…The estimated dose was 1.5 mg/kg/d based on average daily consumption of 190 g of chow/kg of body weight (http://www.researchdiets.com/resource-center-page/typical-food-intake). Previous studies showed that chronic treatment with this dose resulted in GS967 plasma and brain concentrations of 1.0 ± 0.08 and 1.7 ± 0.1 μmol·L –1 , respectively . Chronic treatment with GS967 at 1.5 mg/kg/d did not cause overt adverse neurobehavioral or sedating effects in WT C3HeB/FeJ at 5‐7 weeks of treatment (Figure ).…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…The estimated dose was 1.5 mg/kg/d based on average daily consumption of 190 g of chow/kg of body weight (http://www.researchdiets.com/resource-center-page/typical-food-intake). Previous studies showed that chronic treatment with this dose resulted in GS967 plasma and brain concentrations of 1.0 ± 0.08 and 1.7 ± 0.1 μmol·L –1 , respectively . Chronic treatment with GS967 at 1.5 mg/kg/d did not cause overt adverse neurobehavioral or sedating effects in WT C3HeB/FeJ at 5‐7 weeks of treatment (Figure ).…”
Section: Methodsmentioning
confidence: 71%
“…Vehicle control mice were administered either vegetable oil or 0.5% methyl cellulose in water. For chronic administration studies, mice were fed Purina 5001 rodent chow compounded with GS967 (8 mg/kg of chow; Research Diets, New Brunswick, NJ, USA) . The estimated dose was 1.5 mg/kg/d based on average daily consumption of 190 g of chow/kg of body weight (http://www.researchdiets.com/resource-center-page/typical-food-intake).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PV INs are essential for generating gamma oscillations and for suppressing hypersynchronous network activity, an impairment in PV IN function shared among different mouse models of AD and present during the initial stages of the disease may have highly relevant clinical and therapeutic consequences. The development of specific Na + channel modulators is an obvious start in this direction (Anderson et al, 2017; Frederiksen et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two recent papers have highlighted the antiepileptic effects of two drugs known to inhibit cardiac sodium channels (18,19). Ranolazine, a specific inhibitor of persistent sodium currents and an FDA-approved drug for angina pectoris, reduced seizure frequency by approximately 50% in the gain of function Scn2a Q54 mouse, however GS967, a novel compound with greater inhibition of persistent sodium currents, decreased seizure frequency by more than 90% and increased survival, in addition to preventing neuron loss in the dentate hilus and suppressing mossy fiber sprouting in the dentate gyrus (18).…”
Section: Kcna1mentioning
confidence: 99%